Proton exchange membrane electrolytic cell membrane electrode with porous structure as well as preparation method and application of proton exchange membrane electrolytic cell membrane electrode

By using ammonium salts and water-soluble polymer pore-forming agents in the membrane electrode of the proton exchange membrane electrolytic cell, a porous structure is formed, which solves the problem of water gas mass transfer at high current density in electrolyzing hydrogen production, and improves hydrogen production efficiency and membrane electrode performance.

CN119800390APending Publication Date: 2025-04-11SUZHOU LABORATORY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411771414.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, it is difficult to achieve effective water-gas mass transfer at high current density in electrolyzed hydrogen production, resulting in a decrease in the performance of the anode catalytic layer and a decrease in the hydrogen production efficiency.

Method used

An ammonium salt pore-forming agent and a water-soluble polymer pore-forming agent are used to mix with an anode catalyst and perfluorosulfonic acid resin, and then heat-press transfer is combined with a proton exchange membrane after ultrasonic treatment to form a proton exchange membrane electrolytic membrane electrode with a porous structure.

Benefits of technology

The optimization of water gas mass transfer at high current density is achieved, the working performance and hydrogen production efficiency of the membrane electrode are improved, and the preparation method is simple and fast, safe and efficient, and no impurities or pollutants are introduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800390A_ABST
    Figure CN119800390A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of water electrolysis hydrogen production, and particularly relates to a proton exchange membrane electrolytic cell membrane electrode with a porous structure and a preparation method and application thereof. According to the porous structure membrane electrode, a cathode catalyst layer and a porous anode catalyst layer are arranged on the two sides of a proton exchange membrane respectively; mixing an anode catalyst, a perfluorosulfonic acid resin solution, a first solvent and a pore-forming agent solution to obtain anode catalyst slurry; mixing a cathode catalyst, a perfluorosulfonic acid resin solution and a second solvent to obtain cathode catalyst slurry; and respectively spraying the catalyst slurry onto a substrate, carrying out hot-press transfer molding together with a proton exchange membrane, and removing the solvent and the pore-forming agent to obtain the membrane electrode of the proton exchange membrane electrolytic cell with a porous structure. The preparation method of the membrane electrode provided by the invention is simple, rapid, safe and efficient, pollutants and impurities are not introduced, and a rich porous structure is introduced into the anode catalyst layer, so that water-gas mass transfer under high current density is remarkably optimized, and the working performance of the membrane electrode is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of hydrogen production by electrolysis of water, and in particular relates to a proton exchange membrane electrolyzer membrane electrode with a porous structure, and a preparation method and application thereof. Background Art

[0002] With the gradual depletion of traditional fossil energy, the development of new energy sources is imminent. Among them, hydrogen energy is a new energy source with high energy density and conversion efficiency and is environmentally friendly and pollution-free, which has attracted widespread attention from researchers. Among all the current hydrogen production methods, water electrolysis is the most effective method to obtain green hydrogen. Among them, proton exchange membrane water electrolysis (PEMWE) hydrogen production technology has higher hydrogen production efficiency and purity, and can achieve a larger operating current density and higher adaptability to fluctuating power sources, and has good development prospects and commercial value.

[0003] In the PEMWE hydrogen production technology, the electrolyzer is a crucial part. In the electrolyzer, the design of the membrane electrode, especially the anode catalyst layer, is the key to achieving long-term stable and efficient hydrogen production. Under the high current density working conditions required by industry, the output of oxygen in the anode is huge. If it cannot be discharged quickly, it will not only cover the effective active sites of the catalyst, but also cause the reactant water to be unable to be supplied to the catalyst surface in time, eventually leading to a decrease in reaction performance and a sharp increase in working voltage, which has a fatal impact on hydrogen production efficiency and cost. In the traditional membrane electrode preparation process, due to process and technical reasons, the anode catalyst layer basically does not have a rich pore structure, or it will form "inefficient pores" with small pore sizes and non-through "ineffective pores", which will lead to the obstruction of mass transfer at high current density, and the discharge of oxygen and the supply of water will become difficult. The performance of the electrolyzer will also decrease, and the hydrogen production efficiency will be reduced. Therefore, it is crucial for PEMWE technology and its application to reasonably design the structure of the anode catalyst layer and form a pore structure that is conducive to mass transfer.

[0004] Chinese patent CN115275216B discloses a pore-forming composition and its application for pore-forming in the catalyst layer of a fuel cell, which mainly includes the following steps: mixing a solid catalyst, an ionic polymer, a pore-forming composition and a solvent to obtain a catalyst slurry; applying the catalyst slurry to a substrate to obtain a first blank; catalyzing the decarboxylation of the pore-forming agent component of the first blank to achieve pore-forming to obtain a second blank; post-processing the second blank to obtain a catalyst layer. However, in the process of preparing the membrane electrode, the pore-forming composition needs to be photocatalytically decarboxylated to achieve the pore-forming effect, and the remaining pore-forming composition is removed by post-processing. The whole process is complicated and time-consuming, and impurities are easily introduced into the membrane electrode. In addition, the pore-forming composition and subsequent impregnation treatment require the use of organic substances such as dihydropyridine and toluene, which are very toxic and will harm the health of the experimenters. On the other hand, the cathode and anode catalysts of the fuel cell membrane electrode are both platinum carbon. Under working conditions, hydrogen and oxygen are introduced into both sides respectively. While considering the effective transmission of gas to the surface of the catalyst layer, the "flooding" problem should be avoided. The anode catalyst of the membrane electrode for hydrogen production by water electrolysis generally uses iridium-based oxides. Under working conditions, deionized water is introduced into the anode, while no gas or water is introduced into the cathode. Therefore, the anode needs to consider the timely supply of reactant water to the surface of the catalyst layer and the rapid discharge of product oxygen. The mass transfer requirements of the two for water and gas are completely opposite, so the pore-forming effect of the catalyst layer in the fuel cell may not be applicable to the hydrogen production system by water electrolysis.

[0005] Chinese patent CN115011986A uses one or more of SiO2, CaCO3, CuO and MgO as pore-forming agents. The treatment method is to spray the slurry on the proton exchange membrane, and then immerse the prepared membrane electrode in dilute sulfuric acid and deionized water in turn to etch the corresponding pore-forming agent to form pores. This method is not only cumbersome and inefficient, but also produces corresponding impurity cations during the pickling process, which will inevitably pollute the proton exchange membrane and affect the performance and hydrogen production efficiency of the entire membrane electrode. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a proton exchange membrane electrolyzer membrane electrode with a porous structure, and a preparation method and application thereof. The preparation method of the membrane electrode is simple, fast, safe and efficient, and does not introduce pollutants and impurities. The prepared proton exchange membrane electrolyzer membrane electrode has a rich pore structure, which is conducive to water vapor transmission under high current density and has high activity when applied to PEMWE.

[0007] In order to solve the above-mentioned technical problems, this application provides the following technical solutions:

[0008] The present invention provides a method for preparing a proton exchange membrane electrolyzer membrane electrode having a porous structure, comprising the following steps:

[0009] S1: mixing an anode catalyst, a hydroalcoholic solution of a perfluorosulfonic acid resin, a first solvent and a pore-forming agent solution, and subjecting the mixture to ultrasonic treatment to obtain an anode catalyst slurry; the solvent in the pore-forming agent solution is the first solvent, and the pore-forming agent is selected from one or more of an ammonium salt pore-forming agent and a water-soluble polymer pore-forming agent; the ammonium salt pore-forming agent is selected from ammonium carbonate, ammonium bicarbonate or ammonium oxalate, and the water-soluble polymer pore-forming agent is selected from polyethylene glycol (PEG), polyvinyl pyrrolidone (PVP) or polyvinyl alcohol (PVA);

[0010] S2: mixing the cathode catalyst, the aqueous alcohol solution of the perfluorosulfonic acid resin and the second solvent, and ultrasonically treating the mixture to obtain a cathode catalyst slurry;

[0011] S3: Spraying the cathode catalyst slurry and the anode catalyst slurry onto different substrates respectively, and hot-pressing and transferring them together with the proton exchange membrane to obtain the proton exchange membrane electrolyzer membrane electrode with a porous structure.

[0012] In the preparation method of the present invention, cathode and anode slurries are prepared and sprayed onto the substrate material respectively, and hot-pressed and transferred together with the proton exchange membrane to form the membrane electrode, and the solvent and pore-forming agent are removed to obtain a proton exchange membrane electrolyzer membrane electrode with a porous structure.

[0013] Preferably, the anode catalyst is selected from one or more of Ir black, crystalline IrO2 and amorphous IrOx, the cathode catalyst is Pt / C, and the perfluorosulfonic acid resin is selected from Nafion D520.

[0014] Furthermore, in step S2, the mass ratio of the perfluorosulfonic acid resin to the C in the cathode catalyst (I / C ratio) is 0.7-1:1.

[0015] Preferably, the first solvent and the second solvent are both solvents formed by mixing water and a low-boiling alcohol, and the low-boiling alcohol is selected from one or more of methanol, ethanol, n-propanol and isopropanol; in the first solvent, the volume ratio of water to the low-boiling alcohol is 1:1-4; in the second solvent, the volume ratio of water to the low-boiling alcohol is 1:3-6.

[0016] Preferably, in step S1, the mass ratio of the anode catalyst, the perfluorosulfonic acid resin, the first solvent and the pore-forming agent is 1: 0.05-0.2: 100-200: 0.1-0.5.

[0017] Preferably, in step S1, the ultrasonic treatment method is ultrasonic treatment in an ice-water bath for 60-120 min; in step S2, the ultrasonic treatment method is ultrasonic treatment in an ice-water bath for 30-90 min.

[0018] Preferably, the substrate is selected from polytetrafluoroethylene (PTFE), and the proton exchange membrane is selected from one of Nafion115, Nafion117, Nafion212 or GORE M275.80.

[0019] Preferably, in step S2, the mass ratio of the cathode catalyst to the second solvent is 1:50-150.

[0020] Preferably, in step S3, the temperature of the hot pressing transfer molding is 120-160° C., the pressure is 0.5-5 MPa, and the time is 2-10 min.

[0021] Preferably, in the proton exchange membrane electrolyzer membrane electrode having a porous structure, the loading amount of the anode catalyst Ir is 0.2-1 mg Ir / cm 2 , the cathode catalyst Pt loading is 0.1-0.5 mg Pt / cm 2 .

[0022] The present invention also provides a proton exchange membrane electrolyzer membrane electrode with a porous structure prepared by the above preparation method.

[0023] The proton exchange membrane electrolyzer membrane electrode has a rich pore structure.

[0024] The present invention also provides an application of the above-mentioned proton exchange membrane electrolyzer membrane electrode with a porous structure in hydrogen production by electrolyzing water.

[0025] The technical solution of the present invention has the following advantages over the prior art:

[0026] Compared with the prior art, the present invention provides a proton exchange membrane electrolyzer membrane electrode with a porous structure, which is applied to a water electrolysis hydrogen production device, can optimize water-gas mass transfer under high current density, and realize high-performance and efficient hydrogen production; its preparation method mainly comprises the following steps: firstly preparing cathode and anode slurries, wherein a pore-forming agent is added to the anode catalyst slurry, wherein the pore-forming agent is selected from one or more of ammonium salt pore-forming agents and water-soluble polymer pore-forming agents, and then the catalyst slurries are sprayed onto a substrate material respectively, and are heat-pressed and transferred together with a proton exchange membrane to form, and the solvent and the pore-forming agent are removed to obtain a proton exchange membrane electrolyzer membrane electrode with a porous structure.

[0027] The preparation method of the present invention is simple, fast, safe and efficient, and does not introduce any impurities and pollutants. The pore former adopts one or more of an ammonium salt pore former and a water-soluble polymer pore former, wherein the ammonium salt pore former can be removed by being decomposed into gas by heat during the hot pressing process of preparing the membrane electrode, and the water-soluble polymer pore former can be removed by flushing with flowing water during the activation process of the membrane electrode performance test, and no additional pore former and cleaning steps need to be introduced, which is simple, fast, safe and efficient, and leaves a rich pore structure in the anode catalyst layer. This pore structure is conducive to the timely supply of reactant water and the rapid discharge of product oxygen under the high current density working conditions of the electrolytic water hydrogen production electrolyzer, optimizes water gas mass transfer, and thus improves the working performance of the membrane electrode. At the same time, the two types of pore formers will not produce impurities that can contaminate the membrane electrode during the natural removal process, and therefore will not cause the decline of the electrolyzer performance, thereby maintaining a higher hydrogen production efficiency.

[0028] The proton exchange membrane electrolyzer membrane electrode with a porous structure prepared by the present invention has high activity when used in hydrogen production by electrolysis of water and has broad industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a SEM image of the surface of the anode catalyst layer of the membrane electrode prepared in Example 1;

[0030] Figure 2 This is a SEM image of the surface of the anode catalyst layer of the membrane electrode prepared in Comparative Example 1;

[0031] Figure 3 The performance comparison diagram of the electrolyzer assembled with the membrane electrode prepared in Example 1, Example 2 and Comparative Example 1;

[0032] Figure 4 The performance comparison chart of the electrolyzer assembled with the membrane electrode prepared in Example 3 and Comparative Example 2 is shown. DETAILED DESCRIPTION

[0033] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0034] Among them, the raw materials involved in the embodiments of the present invention are commercially available.

[0035] Example 1

[0036] The steps for preparing the membrane electrode of the proton exchange membrane electrolyzer with a porous structure in this embodiment are as follows:

[0037] 1. Preparation of anode catalyst slurry

[0038] 50 mg of amorphous IrOx anode catalyst was weighed and added to 8 mL of a mixed first solvent of deionized water and isopropanol (volume ratio of 1:3). At the same time, 60 mg of NH4HCO3 pore former was weighed and dissolved in 8 mL of the first solvent. Subsequently, 1.6 mL of the pore former solution and 140 μL of Nafion D520 perfluorosulfonic acid resin solution were added to the initial catalyst slurry. The mixture was ultrasonically treated in an ice-water bath for 90 min to obtain an anode catalyst slurry.

[0039] 2. Preparation of cathode catalyst slurry

[0040] 100 mg of 46.7 wt% Pt / C cathode catalyst was weighed and added to 10 mL of a mixed second solvent of deionized water and isopropanol (volume ratio of 1:4), and then 1 mL of Nafion D520 perfluorosulfonic acid resin solution was added thereto. The mixture was ultrasonically treated in an ice-water bath for 60 min to obtain a cathode catalyst slurry.

[0041] 3. Preparation of membrane electrode

[0042] The cathode and anode catalyst slurries prepared in steps 1 and 2 were ultrasonically sprayed on the PTFE substrate respectively. The proton exchange membrane used Nafion 115 membrane and sandwiched it between the two PTFE sheets mentioned above. Then it was placed in a transfer mold and the entire mold was placed in a hot press. The hot press transfer molding was performed at 135°C and 2MPa for 3 minutes to obtain a proton exchange membrane electrolyzer membrane electrode with a porous structure. The Ir loading in the final membrane electrode anode catalyst was 0.5mg. Ir / cm 2 , the Pt loading in the cathode catalyst is 0.2 mg Pt / cm 2 .

[0043] Example 2

[0044] 1. Preparation of anode catalyst slurry

[0045] Weigh 50 mg of amorphous IrO x The anode catalyst was added to 8 mL of a mixed first solvent of deionized water and isopropanol (volume ratio of 1:3). At the same time, 60 mg of PEG (MW1000) pore former was weighed and dissolved in 8 mL of the first solvent. Subsequently, 0.8 mL of the pore former solution and 140 μL of Nafion D520 perfluorosulfonic acid resin solution were added to the initial catalyst slurry, and the mixture was ultrasonically treated in an ice-water bath for 90 min to obtain an anode catalyst slurry.

[0046] 2. Preparation of cathode catalyst slurry

[0047] 100 mg of 46.7 wt% Pt / C cathode catalyst was weighed and added to 10 mL of a mixed second solvent of deionized water and isopropanol (volume ratio of 1:4), and then 1 mL of Nafion D520 perfluorosulfonic acid resin solution was added thereto. The mixture was ultrasonically treated in an ice-water bath for 60 min to obtain a cathode catalyst slurry.

[0048] 3. Preparation of membrane electrode

[0049] The cathode and anode catalyst slurries prepared in steps 1 and 2 were ultrasonically sprayed on the PTFE substrate respectively. The proton exchange membrane used Nafion 115 membrane and sandwiched it between the two PTFE sheets mentioned above. Then it was placed in a transfer mold and the entire mold was placed in a hot press. The hot press transfer molding was performed at 135°C and 2MPa for 3 minutes to obtain a proton exchange membrane electrolyzer membrane electrode with a porous structure. The Ir loading in the final membrane electrode anode catalyst was 0.5mg. Ir / cm 2 , the Pt loading in the cathode catalyst is 0.2 mg Pt / cm 2 .

[0050] Example 3

[0051] 1. Preparation of anode catalyst slurry

[0052] The anode catalyst slurry preparation is the same as that in Example 1.

[0053] 2. Preparation of cathode catalyst slurry

[0054] The cathode catalyst slurry preparation is the same as that in Example 1.

[0055] 3. Preparation of membrane electrode

[0056] The cathode and anode catalyst slurries prepared in steps 1 and 2 were ultrasonically sprayed on the PTFE substrate respectively. The proton exchange membrane used Nafion 212 membrane and sandwiched it between the two PTFE sheets. Then it was placed in a transfer mold and the entire mold was placed in a hot press. The hot press transfer molding was performed at 135°C and 2MPa for 3 minutes to obtain a proton exchange membrane electrolyzer membrane electrode with a porous structure. The Ir loading in the final membrane electrode anode catalyst was 0.5mg Ir / cm 2 , the Pt loading in the cathode catalyst is 0.2 mg Pt / cm 2 .

[0057] Comparative Example 1

[0058] 1. Preparation of anode catalyst slurry

[0059] Weigh 50 mg of amorphous IrO x The anode catalyst was added to 8 mL of a mixed first solvent of deionized water and isopropanol (volume ratio of 1:3), and then 140 μL of Nafion D520 perfluorosulfonic acid resin solution was added thereto, and ultrasonic treatment was performed in an ice-water bath for 90 min to obtain an anode catalyst slurry.

[0060] 2. Preparation of cathode catalyst slurry

[0061] 100 mg of 46.7 wt% Pt / C cathode catalyst was weighed and added to 10 mL of a mixed second solvent of deionized water and isopropanol (volume ratio of 1:4), and then 1 mL of Nafion D520 perfluorosulfonic acid resin solution was added thereto. The mixture was ultrasonically treated in an ice-water bath for 60 min to obtain a cathode catalyst slurry.

[0062] 3. Preparation of membrane electrode

[0063] The cathode and anode catalyst slurries prepared in steps 1 and 2 were ultrasonically sprayed on the PTFE substrate respectively. The proton exchange membrane used Nafion 115 membrane and sandwiched it between the two PTFE sheets. Then it was placed in a transfer mold and the entire mold was placed in a hot press. The hot press transfer molding was performed at 135°C and 2MPa for 3 minutes to obtain a proton exchange membrane electrolyzer membrane electrode. The Ir loading in the final membrane electrode anode catalyst was 0.5mg Ir / cm 2 , the Pt loading in the cathode catalyst is 0.2 mg Pt / cm 2 .

[0064] Comparative Example 2

[0065] 1. Preparation of anode catalyst slurry

[0066] The anode catalyst slurry preparation is the same as that of Comparative Example 1.

[0067] 2. Preparation of cathode catalyst slurry

[0068] The cathode catalyst slurry preparation is the same as that of Comparative Example 1.

[0069] 3. Preparation of membrane electrode

[0070] The cathode and anode catalyst slurries prepared in steps 1 and 2 were ultrasonically sprayed on the PTFE substrate respectively. The proton exchange membrane used Nafion 212 membrane and sandwiched it between the two PTFE sheets. Then it was placed in a transfer mold and the entire mold was placed in a hot press. The hot press transfer molding was performed at 135°C and 2MPa for 3 minutes to obtain a proton exchange membrane electrolyzer membrane electrode with a porous structure. The Ir loading in the final membrane electrode anode catalyst was 0.5mg Ir / cm 2 , the Pt loading in the cathode catalyst is 0.2 mg Pt / cm 2 .

[0071] Effect evaluation 1

[0072] Figure 1 The SEM image of the surface of the anode catalyst layer of the membrane electrode prepared in Example 1 is shown. Figure 2 The SEM image of the anode catalyst layer surface of the membrane electrode prepared in Comparative Example 1 is shown. By comparing the two images, it can be found that the anode catalyst layer surface of the membrane electrode Example 1 prepared by adding a pore-forming agent has a rich pore structure, and the pore size is basically maintained between 100 and 300 nm. However, the pore structure of the anode catalyst layer surface of the membrane electrode Comparative Example 1 prepared without adding a pore-forming agent is very small, and is basically "invalid pores".

[0073] Figure 3 The performance comparison diagram of the electrolyzer assembled with the membrane electrode (using Nafion115 proton exchange membrane) prepared in Example 1, Example 2 and Comparative Example 1 is shown. It can be seen from the figure that at a relatively low current density (<2A / cm 2 ), the performance of the three membrane electrodes is similar, but with the increase of current density, Example 1 and Example 2 with the addition of pore-forming agent still maintain high performance, while the performance of Comparative Example 1 without the addition of pore-forming agent is relatively poor. 2 At the current density of 2.5V, the working voltages of Example 1, Example 2 and Comparative Example 1 were 2.007V, 2.038V and 2.114V respectively. When the upper limit of the system working voltage was 2.2V, the current densities of the three reached 4.15A / cm 2 , 3.57A / cm 2 and 3.15A / cm 2 . Figure 4 The performance comparison diagram of the electrolyzer assembled by the membrane electrode (using Nafion212 proton exchange membrane) prepared in Example 3 and Comparative Example 2 is shown. Similarly, it can be seen from the figure that at a relatively low current density (<4A / cm 2), the performance of the two membrane electrodes is basically the same, but with the increase of current density, Example 3 with the addition of pore-forming agent has better performance than Comparative Example 2 without the addition of pore-forming agent. 2 At a current density of 2.5 V, the working voltages of Example 3 and Comparative Example 2 were 2.10 V and 2.16 V, respectively. When the upper limit of the system working voltage was 2.2 V, the current densities of the two were 10.32 A / cm 2 and 9.49A / cm 2 . The above results show that the membrane electrode prepared by adding pore-forming agent has a rich pore structure. This pore structure is conducive to the timely supply of reactant water and the rapid discharge of product oxygen under the high current density working conditions of the water electrolysis hydrogen production electrolyzer, which optimizes the water-gas mass transfer and improves the working performance of the membrane electrode. In addition, the performance change trend of the membrane electrode preparation method applied to different proton exchange membranes is consistent, indicating that the method has a certain universality, which provides certain guidance for the preparation of proton exchange membrane electrolyzer membrane electrodes with porous structures in the future, which is of great significance.

[0074] In summary, the present invention provides a method for preparing a proton exchange membrane electrolyzer membrane electrode with a porous structure, comprising the following steps: mixing an anode catalyst, a perfluorosulfonic acid resin solution, a first solvent and a pore-forming agent solution to obtain an anode catalyst slurry; mixing a cathode catalyst, a perfluorosulfonic acid resin solution and a second solvent to obtain a cathode catalyst slurry; spraying the catalyst slurry onto a substrate respectively, hot pressing and transferring together with a proton exchange membrane, removing the solvent and the pore-forming agent, and obtaining a proton exchange membrane electrolyzer membrane electrode with a porous structure. The preparation method described in the present invention is simple, fast, safe and efficient, and does not introduce any impurities and pollutants. The pore-forming agent is completely decomposed into gas and completely removed during the hot pressing and transferring molding process, and leaves a rich pore structure in the anode catalyst layer. This pore structure is conducive to water-gas mass transfer under high current density, thereby improving the working performance of the electrolyzer.

[0075] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A method for preparing a proton exchange membrane electrolyzer membrane electrode having a porous structure, characterized in that: The following steps are involved: S1: mixing an anode catalyst, a hydroalcoholic solution of a perfluorosulfonic acid resin, a first solvent and a pore-forming agent solution, and subjecting the mixture to ultrasonic treatment to obtain an anode catalyst slurry; the solvent in the pore-forming agent solution is the first solvent, and the pore-forming agent is selected from one or more of an ammonium salt pore-forming agent and a water-soluble polymer pore-forming agent; the ammonium salt pore-forming agent is selected from ammonium carbonate, ammonium bicarbonate or ammonium oxalate, and the water-soluble polymer pore-forming agent is selected from polyethylene glycol, polyvinyl pyrrolidone or polyvinyl alcohol; S2: mixing the cathode catalyst, the aqueous alcohol solution of the perfluorosulfonic acid resin and the second solvent, and ultrasonically treating the mixture to obtain a cathode catalyst slurry; S3: Spraying the cathode catalyst slurry and the anode catalyst slurry onto different substrates respectively, and hot-pressing and transferring them together with the proton exchange membrane to obtain the proton exchange membrane electrolyzer membrane electrode with a porous structure.

2. The preparation method according to claim 1, characterized in that The anode catalyst is selected from one or more of Ir black, crystalline IrO2 and amorphous IrOx, the cathode catalyst is Pt / C, and the perfluorosulfonic acid resin is selected from Nafion D520.

3. The preparation method according to claim 2, characterized in that: In the step S2, the mass ratio of the perfluorosulfonic acid resin to the C in the cathode catalyst is 0.7-1:

1.

4. The preparation method according to claim 1, characterized in that: The first solvent and the second solvent are both solvents formed by mixing water and a low-boiling-point alcohol, and the low-boiling-point alcohol is selected from one or more of methanol, ethanol, n-propanol and isopropanol; in the first solvent, the volume ratio of water to the low-boiling-point alcohol is 1:1-4; in the second solvent, the volume ratio of water to the low-boiling-point alcohol is 1:3-6.

5. The preparation method according to claim 1, characterized in that: In the step S1, the mass ratio of the anode catalyst, the perfluorosulfonic acid resin, the first solvent and the pore-forming agent is 1: 0.05-0.2: 100-200: 0.1-0.

5.

6. The preparation method according to claim 1, characterized in that: In the step S2, the mass ratio of the cathode catalyst to the second solvent is 1:50-150.

7. The preparation method according to claim 1, characterized in that: In step S3, the temperature of the hot pressing transfer molding is 120-160° C., the pressure is 0.5-5 MPa, and the time is 2-10 min.

8. The preparation method according to claim 1, characterized in that: In the proton exchange membrane electrolyzer membrane electrode with a porous structure, the loading amount of the anode catalyst Ir is 0.2-1 mg Ir / cm 2 , the cathode catalyst Pt loading is 0.1-0.5 mg Pt / cm 2 .

9. A proton exchange membrane electrolyzer membrane electrode having a porous structure prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the proton exchange membrane electrolyzer membrane electrode with a porous structure as claimed in claim 9 in hydrogen production by electrolysis of water.

Citation Information

Patent Citations

  • Electrolytic cell membrane electrode with controllable and adjustable pore structure as well as preparation method and application of electrolytic cell membrane electrode

    CN115011986A

  • A pore-forming composition and its application

    CN115275216B